Science Communication Meets Consumer Relations: An Analysis of Twitter Use by 23andMe. Issue 2 (April 2020) - Lee, Nicole M.; Abitbol, Alan; VanDyke, Matthew S.
For-profit organizations play a considerable role in the dissemination of scientific research and information. In the case of direct-to-consumer genetic testing, this is important because how consumers learn about genetic science can influence health decisions and support for science. Through a content analysis of Twitter posts ( N = 1, 000), this study examined how 23andMe balances traditional promotion, communicating product benefits, and sharing scientific research. Results indicated that about half of all posts share science news but sharing science has declined over time. Far fewer posts communicate about the products or their benefits, but these posts garner more retweets and replies.